Penguatan Kelembagaan Pengawas Pemilu di Bawaslu Kabupaten Subang - Hermawan, Herry (Jurnal Pustaka Dianmas, 2025)
This Community Service (PkM) activity aims to strengthen the institutional capacity of the Election Supervisory Agency (Bawaslu) of Subang Regency, particularly in formulating and implementing effective communication strategies The challenges faced by Bawaslu Subang Regency often relate to information dissemination, regulation socialization, and mobilizing community participation in supervision, which depend on communication effectiveness. The PkM method utilized was presentations and discussions, focusing on communication needs analysis, key message design (including violation prevention issues and the use of digital platforms and social media. The training was held on September 15, 2025, at the Laska Hotel, Subang Regency. The results of this activity indicate an increase in participants' understanding of managing public communication. Participants gained the ability to recognize and comprehend better communication techniques, which will serve as a key indicator in increasing active public participation in election supervision in Subang Regency. The recommendation from this activity is the need for Bawaslu Subang Regency to internalize the communication function as a strategic instrument for building public trust and institutional authority within the context of election supervision. This PkM activity is expected to make a contribution to the operational effectiveness of Bawaslu Subang Regency in realizing honest and fair elections.